2017
DOI: 10.1007/s10803-017-3114-4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Listening-Related Stress in School-Aged Children with Autism Spectrum Disorder

Abstract: High levels of stress and anxiety are common in children with Autism Spectrum Disorder (ASD). Within this study of school-aged children (20 male, 6 female) we hypothesised that functional hearing deficits (also pervasive in ASD) could be ameliorated by auditory interventions and that, as a consequence, stress levels would be reduced. The use of Ear-Level Remote Microphone devices and Classroom Amplification systems resulted in significantly improved listening, communication and social interaction and a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 60 publications
2
26
2
Order By: Relevance
“…All children experience stressors of daily life and socializing. However, children with ASD might have increased sensitivity to these stressors due to higher levels of comorbid anxiety and poorer adaptability, social skills, communication skills (van Steensel et al, ), and sensory hypersensitivity (Rance, Chisari, Saunders, & Rault, ; Rogers & Ozonoff, ) than typically‐developing children. Our findings regarding emotional responses resulting from sensory hypersensitivity are supported by other studies on emotional awareness and ASD (Silani et al, ; Thaler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All children experience stressors of daily life and socializing. However, children with ASD might have increased sensitivity to these stressors due to higher levels of comorbid anxiety and poorer adaptability, social skills, communication skills (van Steensel et al, ), and sensory hypersensitivity (Rance, Chisari, Saunders, & Rault, ; Rogers & Ozonoff, ) than typically‐developing children. Our findings regarding emotional responses resulting from sensory hypersensitivity are supported by other studies on emotional awareness and ASD (Silani et al, ; Thaler et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Poon (2012) reports significantly higher scores on the DBC-T anxiety subscale in children with autism than in those with multiple disabilities (p<.001). The other study (Rance et al, 2017) reported teacher scores prepost intervention.…”
Section: Methods Of Collecting Child Anxiety Data From Teachersmentioning
confidence: 99%
“…The majority (81.2%) of studies were observational studies, with the remaining six being intervention studies. Three of the intervention studies were school-based cognitive behavioural therapy (Clarke, Hill & Charman, 2017;Drmic, Aljunied & Reaven, 2017;Luxford, Hadwin & Kovshoff, 2017), one was cognitive-behavioural therapy with some school-based sessions (Fujii et al, 2013), one was a clinic-based cognitive behavioural therapy study (Ooi et al, 2014), and one explored an intervention to reduce listening-related stress and anxiety in the classroom (Rance, Chisari, Saunders & Rault, 2017).…”
Section: Research Team and Study Designmentioning
confidence: 99%
See 2 more Smart Citations